1992
DOI: 10.1111/j.1464-410x.1992.tb15837.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Vacuum Device as Alternative Treatment for Impotence

Abstract: Vacuum erection devices are an acceptable alternative for the management of erectile dysfunction. The safety of such devices has been questioned because of their effects on penile blood flow. We report the use of Doppler ultrasonography to assess arterial flow and its value in ensuring long-term safety of a new external vacuum device. Sixteen patients were studied. At 3 months it was possible to confirm the efficacy and safety of the method and model in 14 patients, 12 of whom had a significant improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In 1996, Seckin et al [23] reported on 32 patients with spinal injury in which neurogenic factors were contributing to ED, fi nding the VED to be a better initial treatment in 22 patients (69%). In a study by Aloui et al [24] on the use of VED as alternative treatment for impotence, 14 neurogenic patients using a VED found signifi cant improvement in sexual function. Similarly, in 1991, Turner et al [15] found improvements with the use of a VED in psychiatric impotence with improved symptomology.…”
Section: Ved As First-line Therapymentioning
confidence: 96%
“…In 1996, Seckin et al [23] reported on 32 patients with spinal injury in which neurogenic factors were contributing to ED, fi nding the VED to be a better initial treatment in 22 patients (69%). In a study by Aloui et al [24] on the use of VED as alternative treatment for impotence, 14 neurogenic patients using a VED found signifi cant improvement in sexual function. Similarly, in 1991, Turner et al [15] found improvements with the use of a VED in psychiatric impotence with improved symptomology.…”
Section: Ved As First-line Therapymentioning
confidence: 96%
“…Following the work of Witherington [ 17] and Nadig [ 18] there has subsequently been a widespread awareness and acceptance by the medical profession of the use of VCDs. However, even as recently as 1988, it was still proposed, even by some of its proponents, as having only a very specific role in improving partial impotence [ 19] or as an interim or alternative to first‐line therapies [ 20]. It was thought to have finally gained recognition with Lue’s commentary in 1990 that ‘I recommend a vacuum constriction device to all of my patients (except those with coagulation disorders and sickle cell) as an initial medical option’ [ 21].…”
Section: Principles Of Treatmentmentioning
confidence: 99%
“…The bands should be removed after a maximum of 30 min, the erection left to subside and if intercourse is to be continued, the whole procedure repeated. Ensuring that this ‘30‐min’ rule is adhered to is important, as studies on cavernosal blood flow with the ring in place have shown significant reductions [ 20, 30–32] and in one report, complete cessation [ 33]. Subsequently, blood‐gas values of cavernosal blood show that it can become markedly ischaemic after this time [ 33], although the brachial/penile pressure index returns to normal within 60 seconds of removing the constriction ring [ 31].…”
Section: Techniquementioning
confidence: 99%
“…Since their introduction, external vacuum devices have been used increasingly for the management of erectile dysfunction (Derouet, 1990;Aloui et al, 1992;Cookson & Nadig, 1993;Derouet & Zehl, 1993;Denil et al, 1996;Wiles, 1998). Since their introduction, external vacuum devices have been used increasingly for the management of erectile dysfunction (Derouet, 1990;Aloui et al, 1992;Cookson & Nadig, 1993;Derouet & Zehl, 1993;Denil et al, 1996;Wiles, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum constriction devices provide a mechanical, non-operative and reversible way of inducing and maintaining an erection. Since their introduction, external vacuum devices have been used increasingly for the management of erectile dysfunction (Derouet, 1990;Aloui et al, 1992;Cookson & Nadig, 1993;Derouet & Zehl, 1993;Denil et al, 1996;Wiles, 1998). Data on acceptance and satisfaction are available for penile prothesis and intracavernosal pharmacotherapy, but are limited for long-term results on use of the external negative pressure devices (Cookson & Nadig, 1993).…”
Section: Introductionmentioning
confidence: 99%